Eve (at Brisbane Powerhouse) 2017 - Brown Ash, Margi; Mercer, Leah (Brisbane Powerhouse, 2017)
Directed by Leah Mercer, Eve is the fictional story of a writer caught somewhere between the domestic and the artistic; a story of a reluctant mother and passionate artist; a story for anyone who's ever felt as if they never belonged. Eve longs to be left alone to interpret the world through her viciously beautiful prose.